2013
DOI: 10.4314/ajtcam.v10i5.13
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of some <i>Euphorbia</i> species

Abstract: In this study, the antimicrobial activities of methanolic extracts and latex of some Euphorbia species used for medical purposes in Turkey were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…In the current study only a limited number of rhizosphere bacteria could be cultured and identified but many other latex-containing Euphorbia spp. have been found to exert antibacterial activity on several bacterial species [ 19 , 33 – 35 ]. Metagenomical studies on the rhizosphere bacteria and fungi of Stipagrostis species and their presence/absence in soil from FCs, the matrix and from underneath dead euphorbias, could prove to be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study only a limited number of rhizosphere bacteria could be cultured and identified but many other latex-containing Euphorbia spp. have been found to exert antibacterial activity on several bacterial species [ 19 , 33 – 35 ]. Metagenomical studies on the rhizosphere bacteria and fungi of Stipagrostis species and their presence/absence in soil from FCs, the matrix and from underneath dead euphorbias, could prove to be interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of 25 µL of the plant extract were evenly applied directly to the wells. Petri plates were stored at 4 °C for 2 h. The bacterial inoculated petri plates were incubated at 37 ± 0.1 °C for 24 h and agar plates inoculated with yeast were incubated at 25 ± 0.1 °C for 48 h. The antimicrobial activity found in the extract was assessed by measuring the zone of inhibition (ZOI) against the test organisms (Kirbag et al, 2013). The extract was tested in triplicate and erythromycin (15 µg) disc was used as a positive control and sterile water as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The ethyl acetate fraction of the methanolic extract of Euphorbia pulcherrima was reported to contain phytochemicals which showed remarkable activities against E. coli , S. aureus , Salmonella typhi , and Pseudomonas aeruginosa (Sharif et al 2011 ). Methanolic extracts and latex of some species of Euphorbia are known to inhibit the growth of S. aureus , Bacillus megaterium , Proteus vulgaris , Klebsiella pneumonia , E. coli , P. aeruginosa and C. albicans (Kirbag et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%